Women's Movements Institutionalization and Impact on Policy. The Case of the Bolivian Movement of Domestic Workers - Castaño, Pablo (PARTECIPAZIONE E CONFLITTO, 2019)
Several authors have analysed how institutionalized women's movements impact policy, but research has devoted little attention to the differentiated impact of institutionalized movements on the substantive and symbolic dimensions of the same policy. I investigate this issue by focusing on the Bolivian movement of domestic workers, a paradigmatic case of an institutionalized women's movement that had a sound impact on the symbolic dimension of the policy on domestic workers' rights but a much weaker impact on its substantive dimension. The research is based on qualitative content analysis of documents produced by the movement and the government, and semi-structured interviews with key actors. I have reached three main findings. First, institutionalization facilitates the achievement of symbolic policy outcomes, but does not necessarily allow the achievement of substantive policy outcomes. Second, the inclusion of movements in deliberative processes that imply the joint elaboration of policy seems to be the form of institutionalization that allows the strongest impact on the substantive dimension of policy, while the appointment of movement members to official positions is less effective. Third, a form of institutionalization that was not included in existent typologies has been identified: the recognition of the importance of a movement by the government.